Control of endothelial cell proliferation and migration by VEGF signaling to histone deacetylase 7 - Wang, Shusheng (National Academy of Sciences, 2008)
VEGF has been shown to regulate endothelial cell (EC) proliferation and migration. However, the nuclear mediators of the actions of VEGF in ECs have not been fully defined. We show that VEGF induces the phosphorylation of three conserved serine residues in histone deacetylase 7 (HDAC7) via protein kinase D, which promotes nuclear export of HDAC7 and activation of VEGF-responsive genes in ECs. Expression of a signal-resistant HDAC7 mutant protein in ECs inhibits proliferation and migration in response to VEGF. These results demonstrate that phosphorylation of HDAC7 serves as a molecular switch to mediate VEGF signaling and endothelial function.